Comparison of Thyroid Hormone Levels Between Patients With Major Depressive Disorder and Healthy Individuals in China - Zhou, Yanan; Ma, Yuejiao; Wu, Qiuxia; Wang, Qianjin; Yang, Winson Fu Zun; Wang, Yunfei; Yang, Dong; Luo, Yinli; Tang, Kewei; Liu, Tieqiao; Wang, Dongfang (Frontiers in Psychiatry, 2021)
Abnormal thyroid function in major depressive disorder (MDD) has long been researched extensively but remains controversial. In China, few studies have investigated the differences in thyroid hormone levels between patients with MDD and healthy controls (HC) in a large sample. In the present study, we compared the levels of thyroid hormones (FT3, FT4, and TSH) in MDD patients (n=535) and HC (n=998), as well as investigated the distribution of thyroid hormone results within and outside normal ranges. Our results showed that all three indicators were significantly lower in MDD patients than in HC. This is also true in different gender and age groups. The rate of population number that outside the normal range in MDD was higher than HC in the three indicators. However, no significant difference was observed in clinical/subclinical hyperthyroidism or hypothyroidism between the two groups. Our study indicated that thyroid hormones levels were reduced in depressed patients. The higher rate of abnormal thyroid function in depressed patients than healthy subjects may confirm the importance of regular monitoring on thyroid function, it also suggests that thyroid hormones may serve as a potential biomarker of depression.